(untitled) (Revista de Ciências Agroveterinárias, 2018)
Meiotic index and palynology were assessed for Eugenia involucrata DC-Myrtaceae, a native species of southern Brazil that presents fruits with commercial potential and medicinal properties. For this purpose, floral buds were collected of different individuals from one population at Campo Erê, Santa Catarina, Brazil, and fixed for analysis. Anthers at different development stages were subjected to several techniques for analysis of meiocytes and pollen grains. The behavior of chromosomes in meiosis was normal, with cells in several phases of the cell cycle. Analysis of meiotic index allowed high cytological stability, with 95% of regular tetrads. The pollen grains were positive-starch and negative-lipid. The pollen viability was higher than 95% in all colorimetric tests. Pollen grains are monads, small, oblate, tricolporate, syncolpate with verrucate ornamentation of exine. The high meiotic stability, presence of reserve substances and pollen morphology evidenced in this study have important implications in the selection of potential genetic material for plant breeding, the understanding of pollinating mechanisms and the biosystematics of the genus.